Advances in biological and medical physics. - Lawrence, John H. (John Hundale), 1904-1991; Tobias, Cornelius A.; Hayes, Thomas L. (Thomas Leo), 1927- (Academic Press, 1960)
Advances in Biological and Medical Physics, Volume VII, provides an overview of the state of knowledge in biological and medical physics. The book opens with a study on genetic and physiological effects of the decay of incorporated radioactive phosphorus in bacterial viruses and bacteria. This is followed by separate chapters on micro x-ray diffraction on biological materials; autoradiography with tritium-labeled substances; mechanisms of activity transfer between receptor cell and nerve cell in the Limulus lateral eye; and the effects of radiation on the central nervous system. Subsequent cha.